Neighborhood Socioeconomic Disadvantage and Childhood Body Mass Index Trajectories From Birth to 7 Years of Age. Issue 1 (January 2022) - Rautava, Samuli; Turta, Olli; Vahtera, Jussi; Pentti, Jaana; Kivimäki, Mika; Pearce, Jamie; Kawachi, Ichiro; Rautava, Päivi; Lagström, Hanna
Abstract : Background: The epidemic of increasing childhood overweight and obesity is a major global health concern, with local contextual factors identified as possible contributors. Robust research is needed to establish an evidence base supporting health policy decisions to reverse the trend. We aimed to examine the association between neighborhood socioeconomic disadvantage and trajectories of body mass index (BMI) from birth to age 7. Methods: The present study included 11, 023 children born within the Southwest Finland Birth Cohort who were free of severe conditions affecting growth with adequate exposure and growth data. We obtained child growth data until school age from municipal follow-up clinics. We based cumulative childhood neighborhood socioeconomic disadvantage on the average annual income, unemployment, and level of education in a residential area defined using a geographic grid at a spatial resolution of 250 m by 250 m. Results: Cumulative neighborhood socioeconomic disadvantage was associated with distinct childhood BMI z score trajectories from birth to age 7. Despite being born in the lowest BMI z scores, children growing up in disadvantaged neighborhoods subsequently exhibited a trajectory of increasing BMI z scores starting at 4 years of age, ending up with a higher risk of overweight at the end of the follow-up (30%) as compared with children living in more affluent neighborhoods (22%). The corresponding risk of obesity was 5 % for those in affluent neighborhoods and 9 % and those in disadvantaged neighborhoods. Conclusion: Cumulative exposure to neighborhood socioeconomic disadvantage is independently associated with unfavorable BMI development and obesity in childhood. Abstract : Supplemental Digital Content is available in the text.